2011
DOI: 10.1016/j.biopsych.2011.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Aversive Imagery in Panic Disorder: Agoraphobia Severity, Comorbidity, and Defensive Physiology

Abstract: Background Panic is characterized as a disorder of interoceptive physiological hyperarousal, secondary to persistent anticipation of panic attacks. The novel aim of the present research was to investigate whether severity of agoraphobia within panic disorder covaries with the intensity of physiological reactions to imagery of panic attacks and other aversive scenarios. Methods A community sample of principal panic disorder (n=112; 41 without agoraphobia, 71 with agoraphobia) and control (n=76) participants i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
59
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 74 publications
7
59
2
1
Order By: Relevance
“…Importantly, risk allele carriers reported comparable high subjective distress during the test, which, interestingly, was not linked to autonomic mobilization demonstrating the physiological preparation for behavioral responses during acute threat: While patients carrying the non-risk allele variant showed large correlations between reported anxiety and heart rate response during BAT exposure, risk-allele carriers did not. In line with previous results that demonstrated reduced threat related defensive reactivity in those PD/AG patients reporting pervasive agoraphobic apprehension and avoidance, but also broad dysphoria and general distress 67 , the rs16689918 risk allele was associated with pronounced depressive symptoms (BDI-II), general distress (BSI) and agoraphobic avoidance (MI) in the BAT sample (see supplemental table 3). Therefore rs16689918 might increase the risk for PD by facilitating the development of anxious apprehension.…”
Section: Discussionsupporting
confidence: 90%
“…Importantly, risk allele carriers reported comparable high subjective distress during the test, which, interestingly, was not linked to autonomic mobilization demonstrating the physiological preparation for behavioral responses during acute threat: While patients carrying the non-risk allele variant showed large correlations between reported anxiety and heart rate response during BAT exposure, risk-allele carriers did not. In line with previous results that demonstrated reduced threat related defensive reactivity in those PD/AG patients reporting pervasive agoraphobic apprehension and avoidance, but also broad dysphoria and general distress 67 , the rs16689918 risk allele was associated with pronounced depressive symptoms (BDI-II), general distress (BSI) and agoraphobic avoidance (MI) in the BAT sample (see supplemental table 3). Therefore rs16689918 might increase the risk for PD by facilitating the development of anxious apprehension.…”
Section: Discussionsupporting
confidence: 90%
“…The controversial results could also be connected to differential physiological reactivity among panic patients even before the therapeutic intervention. McTeague et al (2011) showed increased reactivity in panic patients without, or with moderate, agoraphobia; but observed reduced reactivity to startle probe in panic patients with severe agoraphobia.…”
Section: General Resultsmentioning
confidence: 84%
“…We emphasize, however, that the conceptual issues apply to all psychophysiological studies that correlate individual difference measures with subtraction-based difference scores-a practice that is actually quite common. For instance, recent studies in emotion often subtract neutral from emotional condition averages to quantify individual differences in emotional reactivity (Angus, Kemkes, Schutter, & Harmon-Jones, 2015;Bress, Meyer, & Hajcak, 2015;Burkhouse, Siegle, Woody, Kudinova, & Gibb, 2015;Hoenen, L€ ubke, & Pause, 2015;Kornilov, Magnuson, Rakhlin, Landi, & Grigorenko, 2015;McTeague, Lang, Laplante, & Bradley, 2011;Meyer, Hajcak, Torpey-Newman, Kujawa, & Klein, 2015;Sylvester, Hudziak, Gaffrey, Barch, & Luby, 2015). Indeed, current recommendations from experts in the field involve "isolating components of interest by creating [subtraction-based] difference waves" (Luck, 2014).…”
mentioning
confidence: 99%